The Future of the Indo-Pacific Security Architecture: A Scenario Planning Approach in Response to U.S. Foreign Policy in the Age of Trump 2.0 - Meyta Saraswaty Putri (Riviera Publishing, 2025)
President Donald Trump's second presidency marks a significant shift in the foreign policy orientation of the United States, which has had a far-reaching impact on the security configuration in the Indo-Pacific region. This study aims to analyze the impact of Donald Trump's leadership on U.S. foreign policy and its implications for the security dynamics of the Indo-Pacific region. Using a literature review approach and scenario planning framework, this study examines the adaptive responses of countries in the Indo-Pacific region in the face of geopolitical uncertainty posed by Trump's unilateralist and